3D-Printed SARS-CoV-2 RNA Genosensing Microfluidic System - Crevillen, Agustín G; Mayorga-Martinez, Carmen C; Vaghasiya, Jayraj V; Pumera, Martin (Advanced materials technologies, 2022)
Additive manufacturing technology, referred as 3D printing technology, is a growing research field with broad applications from nanosensors fabrication to 3D printing of buildings. Nowadays, the world is dealing with a pandemic and requires the use of simple sensing systems. Here, the strengths of fast screening by a lab-on-a-chip device through electrochemical detection using 3D printing technology for SARS-CoV-2 sensing are combined. This system comprises a PDMS microfluidic channel integrated with an electrochemical cell fully 3D-printed by a 3D printing pen (3D-PP). The 3D-PP genosensor is modified with an ssDNA probe that targeted the N gene sequence of SARS-CoV-2. The sensing mechanism relies on the electro-oxidation of adenines present in ssDNA when in contact with SARS-CoV-2 RNA. The hybridization between ssDNA and target RNA takes a place and ssDNA is desorbed from the genosensor surface, causing a decrease of the sensor signal. The developed SARS-CoV-2/3D-PP genosensor shows high sensitivity and fast response.
Keywords: electroanalysis; additive manufacturing; lab on chip; nucleic acid